Sense of Community and the Bears Ears National Monument - Michael R. Cope; Jaimi Mueller; Carol Ward; Scott R. Sanders; Elizabeth Long-Meek (Land)
This paper used the communities bordering the Bears Ears National Monument, located in rural Southeastern Utah, USA, as a case study to better understand the impact that potential changes in land management have on gateway communities. Our case study is concerned with capturing changes in the sense of community based on discussions concerning potential changes to the community. We employ “psychological sense of community” measures to assess the effect on community residents. Survey data from three gateway communities are modeled using bivariate regressions and ordinary least squares regressions with control variables to assess the four components of PSC against opposition to the proposed changes to the Bears Ears National Monument. We find that potential changes to the land designation significantly affect the respondents’ psychological sense of community. Because public protected areas and gateway communities are linked socioeconomically, environmentally, and culturally, changes in land designations can significantly impact those who live there.